1993
DOI: 10.1111/j.1365-2958.1993.tb01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeat unit polysaccharides of bacteria: a model for polymerization resembling that of ribosomes and fatty acid synthetase, with a novel mechanism for determining chain length

Abstract: We report the identification and sequence from Escherichia coli and Salmonella enterica strains of the cld gene, encoding the chain-length determinant (CLD) which confers a modal distribution of chain length on the O-antigen component of lipopolysaccharide (LPS). The distribution of chain lengths in the absence of this gene fits a model in which as the chain is extended there is a constant probability of 0.165 of transfer of growing chain to LPS core, with termination of chain extension. The data for E. coli O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
180
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(190 citation statements)
references
References 40 publications
10
180
0
Order By: Relevance
“…During LPS Oag biosynthesis, Wzz proteins control Oag modal length distribution through two proposed mechanisms: as a molecular timer of Oag polymerization [9] or in an organizational manner to determine the crucial ratio of the polymerase Wzy to the Oag ligase WaaL [10]. Much of the work aimed at understanding the mechanism behind Wzz-mediated chain length regulation has come from mutagenesis and genetic studies, which revealed that chain modal length regulation is a property of the entire protein [10][11][12][13][14][15][16][17].…”
Section: Wzy-dependent Polysaccharide Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…During LPS Oag biosynthesis, Wzz proteins control Oag modal length distribution through two proposed mechanisms: as a molecular timer of Oag polymerization [9] or in an organizational manner to determine the crucial ratio of the polymerase Wzy to the Oag ligase WaaL [10]. Much of the work aimed at understanding the mechanism behind Wzz-mediated chain length regulation has come from mutagenesis and genetic studies, which revealed that chain modal length regulation is a property of the entire protein [10][11][12][13][14][15][16][17].…”
Section: Wzy-dependent Polysaccharide Biosynthesismentioning
confidence: 99%
“…Much of the work aimed at understanding the mechanism behind Wzz-mediated chain length regulation has come from mutagenesis and genetic studies, which revealed that chain modal length regulation is a property of the entire protein [10][11][12][13][14][15][16][17]. In agreement with secondary structure predictions, genetic and biochemical analyses have shown that Wzz is largely a-helical in structure and is likely to function as an oligomer [9,12,18,19]. These approaches have been limited in giving insight into the molecular mechanism involved in polysaccharide chain modal length control.…”
Section: Wzy-dependent Polysaccharide Biosynthesismentioning
confidence: 99%
“…They have two transmembrane (TM) domains flanking a periplasmic domain (Morona et al, 1995) and a conserved proline-rich region, PX 2 PX 4 SPKX 1 X 10 GGMXGAG, overlapping the second TM region (Becker & Pühler, 1998;Becker et al, 1995;Daniels & Morona, 1999;Morona et al, 2000b). The periplasmic domain of Wzz proteins is predicted to be mostly a-helical in structure (Bastin et al, 1993) and has significant coiled-coil (CC) potential (Morona et al, 2000b). The features described above are illustrated for Wzz pHS2 in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Ugd converts UDP-Glc into UDP-glucuronic acid. In the Enterobacteriaceae, ugd is often located within the OPS biosynthesis gene cluster adjacent to a gene encoding an OPS chain length determinant (wzz) (Amor & Whitfield, 1997;Bastin et al, 1993).…”
Section: Formation Of Activated Sugar Precursorsmentioning
confidence: 99%